Improved Management Teacher Professional Education Program Surabaya State University Through Alumni Tracer (Tracer Study): Pendidikan Profesi Guru (PPG) - Julianto; Fatkur Rohman Kafrawi; Harmanto; Dhani Kristiandri; Mukhzamilah; Fitria Hidayati (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2022)
Abstract: The mandate of Law Number 14 of 2005 concerning Teachers and Lecturers states that teachers are required to have academic qualifications, competencies, educator certificates, physically and mentally healthy, and have the ability to realize national education goals. The preparation of teachers as professional educators is also stated in Government Regulation Number 19 of 2017 concerning Amendments to Government Regulation Number 74 of 2008 concerning Teachers. The State University of Surabaya has been trusted to implement PPG In Position (Daljab) starting in 2018 – now which is being funded by APBN funds. The purpose of this study is to identify and obtain various information related to the level of satisfaction of PPG graduates who participate in PPG activities at the State University of Surabaya. The type of research used is descriptive research. The population in this study is all PPG participants in the range of 2018 - 2020. The samples used in this study are representatives of PPG who have graduated in 2018-2020 for the Madiun, Ngawi and Magetan areas along with the principals where PPG alumni teach. Data collection methods used are interviews and questionnaires. The data obtained will be analyzed descriptively qualitatively and quantitatively. Based on the results and discussion of the data obtained, it can be concluded that the level of management in the implementation of PPG Unesa received a good - very good response. This is indicated by the responses given by PPG Unesa student alumni through a questionnaire distributed using the google form.